The Effect Of Dicipline, Motivation And Leadership Style On The Performance Of Permanent Lecturers With Job Satisfaction As An Intervening Variable At University Abdurachman Saleh Situbondo - Lindrawati; Muhammad Iqbal Anshory; Ratna Koba Susanti (Cita konsultindo, 2025)
Human resources research aims to determine the effect of discipline, motivation and leadership style on the performance of permanent lecturers with an intervening variable, namely the achievement of job satisfaction for permanent lecturers at Abdurachman Saleh University Situbondo. Data collection was carried out on permanent lecturers at Abdurachman Saleh University Situbondo with a population of 95 permanent lecturers and for the use of samples using saturated samples, namely 95 respondents. The data was analyzed by calculating the Partial Least Square (PLS) structural equation system/model from the results of the calculation of the direct effect hypothesis using the Smart PLS 3.0 application. The results of research testing show that (1) Discipline has a positive and significant effect on job satisfaction, (2) Motivation has a positive and significant effect on job satisfaction, (3) Leadership Style has a positive and significant effect on job satisfaction, (4) Discipline has a positive and significant effect on performance, (5) Motivation has a positive and significant effect on performance, (6) Leadership style has a positive and significant effect on performance, (7) Job satisfaction has a positive and significant effect on performance, (8) Discipline has a positive but insignificant effect on performance through job satisfaction as an intervening variable, (9) Motivation has a positive and significant effect on performance through job satisfaction as an intervening variable. and (10) Leadership style has a positive and significant effect on performance through job satisfaction as an intervening variable for permanent lecturers at Abdurachman Saleh University Situbondo.